Histopathological findings in transplanted kidneys. Issue 1 (December 2017) - Katsuma, Ai; Yamakawa, Takafumi; Nakada, Yasuyuki; Yamamoto, Izumi; Yokoo, Takashi
Abstract Improvements in immunosuppression have reduced acute kidney allograft rejection and clinicians are now seeking ways to prolong allograft survival to 20 years and beyond. The primary cause of kidney allograft loss is still chronic rejection, followed by death with a functioning allograft and primary kidney disease recurrence. Thus, overcoming kidney allograft rejection remains the most important issue. Kidney allograft rejection can be classified into two types: T cell- and antibody-mediated rejection. Both are diagnosed pathologically based on the Banff 2013 classification. Other important pathological features in addition to rejection include calcineurin inhibitor toxicity, polyomavirus nephropathy, and recurrence of the primary kidney disease. Here, we review the diagnosis and representative features of histopathological findings in transplanted kidneys.